Examining the fraud diamond theory through ethical culture variables: A study of regional development banks in Indonesia - Dwi Ratmono; Frendy (Cogent Business & Management, 2022)
Previous literature which examined relationship between fraud risk factors and occupational frauds occurrence is limited to the setting of a single developed country. This study aims to bridge this gap by examining the moderating role of ethical culture in affecting the relationship between fraud risks and occupational fraud using the sample of regional development banks (RDB) in one of the major developing countries, Indonesia. Our study employs Indonesian RDBs due to their economic significance and their exposure to a higher risk of occupational fraud. Primary data was collected using a survey method involving 355 employees from the 15 largest RDBs in Indonesia. The collected data was analyzed using the Partial Least Square-Structural Equation Modelling (PLS-SEM). We find that occupational fraud in RDBs is associated with opportunity and pressure. A strong ethical culture can weaken the positive relationship between these two fraud risks and occupational fraud. The findings of our paper imply that organizations that face a significant risk of fraud, such as RDBs, should invest in strengthening the organizations' ethical culture as it could mitigate two out of four fraud risk factors. This study contributes towards development of the fraud diamond theory by examining the effect of ethical culture in mitigating fraud risk in the banking industry which is growing rapidly in a developing economy. This study focuses on a context that has still only been analyzed by previous research to a limited degree, namely RDBs which are known as the "second sector" of the banking industry in Indonesia.
Keywords: 650; ethical culture; fraud risks; moderating role; regional development bank